STATIC RESONANCE IN ROTATING NANOBARS - Guven, Ugur (POLISH SOC THEORETICAL & APPLIED MECHANICS, 2018)
In this study, static resonance that occurs in rotating nanobars is addressed. The analysis is based on Eringen's nonlocal elasticity theory and is performed in Lagrangian coordinates. Explicit solutions are given for both clamped-free and clamped-clamped boundary conditions. The present study shows that the static resonance phenomenon is largely a critical case requiring attention for rotating nanobars with small lengths.
Keywords: rotating nanobar; static resonance; nonlocal elasticity; lagrangian coordinates; INSTABILITY; NANOTUBE; DISKS; RODS; Mechanics